Advances in Corporate Governance Practices in Emerging Economies: A Critical Literature Review - Sultan , Rashid (iRASD Journal of Management, 2024)
Corporate governance (CG) has become a core supporting institution for economic development and corporate and investor confidence in emerging economies undergoing structural transformations. This critical literature review integrates emerging trends in CG practices in the market and emerging areas, including board composition, ownership structure, regulatory reforms, and ESG integration. Based on current empirical works and theoretical approaches, the review highlights accomplishments, identifies underlying persistent institutional and cultural barriers, and identifies research gaps. The paper concludes with a list of recommendations for future studies that can help develop inclusive, transparent, and effective governance practices tailored to the specific needs of emerging economies.